Integrative complexity of wildfire management: the development, use, and implications of a scale - Carroll, Joshua, author; Bright, Alan, advisor; Vaske, Jerry, committee member; Newman, Peter, committee member; Loomis, Ross, committee member (Colorado State University. Libraries, 2005)
Among the challenges and requirements of wildfire management, addressing public perceptions regarding fire suppression techniques is a priority. It has been realized that in order to implement fire management techniques that will have enduring success and support, a skilled assessment of the various publics involved in the decision-making process is imperative. One highly sophisticated method of measuring this public perception is through the use of integrative complexity. Though the traditional methods for measuring integrative complexity are rather tedious for researchers and respondents alike, an alternative, more simplified measure is created and discussed here. The preliminary application and results of this new measure are reported, and there is support for its continued use. The first paper describes the process of designing and testing the scalar instrument, highlighting the methods and scale construction throughout the development. It reviews the logic, construction and testing of the scale, and the results from the pretesting suggest the scale is a good correlate of the traditional measurement technique. The second paper takes this newly-developed scale and utilizes it in a large questionnaire format. It tests integrative complexity's relationship with other constructs such as attitude direction and extremity, as well as exploring previously untested roles as a moderator between value-laden basic beliefs and attitudes. Results of integrative complexity as measured by the scale are similar as to what would be expected based past research, and integrative complexity appears to moderate the basic belief-attitude relationship for certain cases.
Missing page 84 in number only; text folllows.
Keywords: forestry